THERMAL INJECTION PILOT STUDY FOR ULTRA SHALLOW HEAVY OIL FIELD RAS-81 - PITALOKA CITRARASMI (NIM : 22215021), DYAH
RAS-81 field was discovered by drilling exploration wells in 2011. The drilling results showed two potential formation, Telisa and Talang Akar, which were located at shallow depth of between 50-400 ft. Fluid tests showed potential heavy oil with API values of 13-18 API, 600-6,600 cp of viscosity, and low reservoir pressure (40-85 psi). Calculation based on the core and log data resulted in Original Oil in Place (OIP) of over 100 MMBO. The test results also show low production rate, which if used to estimate cumulative oil recovery, only a small fraction of OIP is produced. Worldwide heavy oil production with similar characteristics of RAS-81 was produced by applying thermal injection method. This method is economically and technically interesting since it was able to improve Recovery Factor (RF) higher than primary recovery. Common types of thermal injection is by stimulation (Cyclic Steam Stimulation) or steamflooding. There are several considerations in applying this method in RAS-81, one of which is the shallowness of the formation. This cause the risk of steam eruption becomes higher, since the overlying sediments could not provide sufficient barrier. The other consideration is the limitation of applied injection pressure and volume, since the fracture pressure for the shallow depth formation will be very low. Based on these considerations, a pilot study with reservoir simulation will be conducted. The objective is to select optimum production scenario from several possible scenarios for RAS-81 field.